Integral Numerik: Teknik Analitik dan Numerik dalam Analisis Gelombang dan Osilasi - Erguna Eliandro Junior Tarigan; Alfidorino Flapianus bukit; Rizky Iqna Fitria; Vauline Christin Octavia Siregar (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Mathematically, in calculating oscillations and waves, it can be used using analytical and numerical techniques. For simple movements, numerical techniques are easier to perform than analytical techniques. Because, apart from the difficulty of using analytical techniques, the calculations carried out are also complex. The actual value of a wave or oscillation can be determined using analytical techniques, while numerical techniques are simply calculations carried out close to the analytical value. The aim of this paper is to analyze analytical and numerical techniques in wave and oscillation analysis. The type of research used in this research is based on qualitative research. The results obtained in determining trigonometric integrals require a calculation that can use analytical and numerical techniques. Numerical techniques are calculations that are almost correct or close to the value. However, to get the actual value correctly, analytical calculations are needed. Analytical calculations are quite difficult to do, but need to be done to serve as a reference. The conclusion drawn is that in trigonometric integrals in wave and oscillation analysis, numerical calculation techniques and analytical techniques can be used. When using numerical techniques, you can use formulas , whereas calculations using analytical techniques can use formulas.